AVIATION FUEL SEDIMENTATION DURATION FIXED STANDARD ACCURACY PROBLEMS - E. A. Konyaev; A. I. Timoshenko (Научный вестник МГТУ ГА)
Aviation fuel sedimentation duration fixed standard using problems in fuels and lubricants department are observed.